Diamond film and preparation method and application thereof
By optimizing the ratio of auxiliary gas and crystal surface control, combined with a gradient temperature-controlled deposition strategy, efficient preparation of large-size single-crystal diamond films was achieved, solving the interface defects and high energy consumption problems existing in the existing technology, and obtaining high-performance diamond films.
Patent Information
- Application Number
- CN202511286009.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-10
- Publication Date
- 2025-10-14
- Estimated Expiration
- 2045-09-10
AI Technical Summary
Existing technologies make it difficult to achieve controllable preparation of large-sized single-crystal diamond films, and traditional preparation methods have problems such as high interface defect density, polycrystalline-dominated films, poor thermal stability, slow growth rate and high energy consumption.
By adopting the synergistic effect of in-situ purification of auxiliary gas with optimized ratio and crystal plane regulation, through the dynamic etching-growth balance of chlorine/fluorine auxiliary gas and hydrogen-methane system under high pressure environment, combined with the gradient temperature-controlled deposition strategy, the simultaneous removal of amorphous carbon impurities and the integrated forming of single crystal directional epitaxy are achieved.
High-speed growth of single-crystal diamond films was achieved, interface integrity and thermal stability were improved, energy consumption was reduced, and films with high infrared transmittance, large-size single crystal structure and low defect density were obtained, which are suitable for applications such as high-frequency power devices, electrical sensor chips and infrared optical windows.
Smart Images

Figure CN120776448A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of diamond preparation, and particularly relates to a diamond thin film and a preparation method and application thereof. BACKGROUND
[0002] Diamond not only has high Mohs hardness, but also has many excellent characteristics such as high thermal conductivity, high carrier mobility, wide band gap and breakdown resistance, which makes it gradually show unique natural advantages in the field of national defense and cutting-edge technology, especially in the field of 5G communication high-frequency filter, semiconductor circuit heat dissipation substrate and super-power electronic component heat dissipation packaging, which has irreplaceable application potential, causing great research enthusiasm of scientific researchers. Compared with other semiconductor materials, the preparation of single crystal diamond thin film with large size, low defect and high purity has always been one of the hot issues of general concern.
[0003] At present, people usually adopt mosaic splicing method of homoepitaxy and heteroepitaxy method to realize the preparation of high-quality diamond thin film. However, mosaic splicing method causes interface resistance to increase due to grain orientation deviation, and heteroepitaxy method causes polycrystalline dominance due to lattice mismatch. More seriously, the carrier mobility of polycrystalline diamond thin film is less than 1 / 10 of that of single crystal diamond due to carrier scattering effect at grain boundary, which cannot meet the strict demand of high-precision electrical storage devices on interface conductivity. Therefore, how to realize controllable preparation of large-size single crystal diamond thin film is still a core problem to be solved in this field.
[0004] Invention patent application CN1928151A discloses a preparation method of three-layer diamond thin film with controllable thickness, which belongs to the technical field of chemical vapor deposition process of inorganic non-metallic materials. The existing hot filament chemical vapor deposition experimental device is adopted to adjust and control the parameters such as carbon source concentration, deposition temperature, reaction gas pressure and applied bias, so as to deposit three-layer diamond thin film on a silicon wafer. However, this preparation method uses silicon substrate with lattice mismatch and acetone carbon source, which leads to high interface defect density, polycrystalline dominant thin film and insufficient purity; the three-stage low-pressure deposition process takes too long time, lacks annealing repair mechanism, causes large residual stress of thin film and poor thermal stability, and is difficult to meet the performance demand of single crystal diamond for high-power devices.
[0005] At the same time, the growth speed of diamond thin film material is slow, and the required power consumption is high. Therefore, from the perspective of process optimization, realizing rapid growth of single crystal diamond thin film material under low energy consumption is also one of the hot issues of industry concern.
[0006] In a conventional preparation process, for example, the invention patent CN110724930B provides a preparation method of diamond thin film, which comprises the following steps: placing a pretreated porous metal substrate in a reaction chamber of a hot-wire chemical vapor deposition device, filling the reaction chamber with reaction gas, and allowing the reaction gas to grow on the surface of the porous metal substrate to form a diamond / silicon carbide / metal composite thin film; etching the obtained diamond / silicon carbide / metal composite thin film to remove the metal phase and the silicon carbide phase therein, thereby obtaining a diamond thin film; and calcining the diamond thin film in an oxygen-containing atmosphere to obtain a finished diamond thin film with a hierarchical pore structure. However, the preparation method disclosed in the invention needs to indirectly form a film through a porous metal substrate and relies on multi-step acid etching to remove the metal / silicon carbide phase, resulting in a prolonged process cycle; the growth rate is limited under low-pressure deposition conditions, and the deposition time needs to be significantly prolonged to achieve the target film thickness, which significantly increases power consumption.
[0007] Therefore, how to break through the size limitation of single-crystal diamond thin film growth without multi-step acid etching and heterogeneous substrate, while achieving high-speed and low-energy consumption preparation through deposition process optimization, and ensuring the thermodynamic stability of the diamond phase in subsequent processing, is a problem that needs to be solved by those skilled in the art. SUMMARY
[0008] In view of the defects in the prior art, the present application provides a diamond thin film, a preparation method thereof and an application thereof. The in-situ purification and crystal face regulation of the optimized auxiliary gas are used to realize the synchronous removal of amorphous carbon impurities and the integrated formation of single-crystal directional epitaxy through the dynamic etching-growth balance of chlorine / flourine-containing auxiliary gas and hydrogen-methane system in a high-pressure environment, completely eliminating the damage of multi-step acid etching process to the film structure, and significantly improving the growth rate and interface integrity of single-crystal diamond thin film by combining with the gradient temperature control deposition strategy.
[0009] In a first aspect, the present application provides a preparation method of diamond thin film, comprising the following steps: S1, using a substrate material matching the lattice constant of the diamond thin film material as a substrate, and performing surface treatment on the substrate; S2, introducing a mixed reaction gas comprising 80%-95% hydrogen, 3%-8% methane and 2%-12% auxiliary gas in terms of volume percentage; the auxiliary gas comprises at least one of argon, chlorine, hydrogen fluoride and hydrogen chloride; S3, growing a diamond thin film on the surface of the substrate by controlled chemical vapor deposition at 850-1000℃ and a pressure not less than 21kPa; S4, performing annealing treatment on the diamond thin film.
[0010] The lattice constant matching is that the absolute value of the difference between the lattice constant of the substrate material and the lattice constant of the diamond thin film material is less than 5% of the lattice constant of the diamond thin film material.
[0011] The mixed reaction gas in step S2 can be limited to the combination of the aforementioned gases, that is, the mixed reaction gas is composed of 80%-95% hydrogen, 3%-8% methane and 2%-12% auxiliary gas in terms of volume percentage, preferably, the mixed reaction gas is composed of 85%-91% hydrogen, 3%-5% methane and 6%-10% auxiliary gas.
[0012] In step S3, under the same temperature and pressure conditions, the thickness is basically proportional to the deposition time. According to the application requirements of the thin film, the thickness of the thin film can be controlled by adjusting the process parameters.
[0013] Preferably, the substrate material is selected from natural diamond single crystal, HPHT diamond single crystal or CVD diamond single crystal, and the seed surface is subjected to (100) or (111) crystal face orientation cutting treatment. Selecting a suitable substrate material is conducive to rapid matching and ensuring the matching degree of the lattice constant of the diamond thin film material.
[0014] Preferably, the auxiliary gas is composed of argon, chlorine and hydrogen fluoride in a volume ratio of 1:(0.5-1.5):(0.3-1).
[0015] In the process of preparing a diamond thin film by a conventional chemical vapor deposition (CVD) method, usually only hydrogen and methane are used as the basic reaction gas. Such a system is prone to generate amorphous carbon and graphite phase impurities due to insufficient carbon source cracking or local supersaturation, and the thin film growth interface is gradually polluted by non-diamond phase due to the lack of effective in-situ purification mechanism, finally an additional post-processing step (such as acid etching or plasma etching) is introduced to remove the impurities, which not only significantly increases the process complexity, but also may cause lattice damage or surface roughening problems due to secondary processing.
[0016] In view of this technical bottleneck, the application innovatively introduces an auxiliary gas component, in particular an auxiliary gas combination composed of argon, chlorine and hydrogen fluoride, which synchronously realizes dynamic etching and crystal preferential growth during the deposition process through the synergistic effect of active components (Cl2 / HF) and dilution gas (Ar). The active radicals (Cl· / F·) released by chlorine and hydrogen fluoride at high temperature can preferentially etch amorphous carbon and grain boundary defects, and the etching products (such as CCl4, CF4) escape from the reaction system in the form of gas, thereby forming a self-cleaning effect at the growth interface; argon as a dilution carrier can inhibit the disordered deposition of carbon black and other by-products by adjusting the plasma density and reaction gas partial pressure, and maintain a stable gas phase reaction kinetics environment.
[0017] In particular, the auxiliary gas is proportioned by volume ratio of argon: chlorine: hydrogen fluoride = 1: (0.5-1.5): (0.3-1), which can accurately balance the dynamic relationship between etching rate and deposition rate. Too high proportion of chlorine may lead to over-etching of the single crystal surface, and insufficient proportion of hydrogen fluoride may weaken the purification effect on edge defects. Argon as the main diluent ensures the controllability of the reaction atmosphere. The composite gas system can realize continuous epitaxial growth of high-purity single crystals without relying on post-processing steps, fundamentally solving the dual problems of impurity phase accumulation and process redundancy in traditional processes.
[0018] Preferably, the controlled chemical vapor deposition in step S3 comprises: 1) High-temperature pre-growth: high-temperature pre-growth is carried out at a pre-growth temperature T0 of 950-1000℃, the chamber pressure P0 is maintained at ≥25kPa, preferably the chamber pressure P0 is maintained at ≥27kPa, and the high-temperature pre-growth duration is 25%-55% of the total controlled chemical vapor deposition time; 2) Deposition by reducing temperature: deposition is carried out by gradually reducing the temperature from the pre-growth temperature T0 to the end temperature T1, the end temperature T1 is T0-100℃ to T0-50℃, the chamber pressure P1 is maintained at ≥P0-3kPa, preferably P1 is ≥24kPa.
[0019] Preferably, the controlled chemical vapor deposition comprises at least one of the following conditions: 1) During the high-temperature pre-growth process, periodically introduce boron-containing doped gas, the boron doping concentration is 1×10 18 -5×10 20 cm -3 ; preferably, the on-off cycle is controlled between 5-15min, so that the boron distribution is more uniform; The boron atom as an acceptor doping source can adjust the energy band structure and surface electronic state distribution of diamond, and then affect the lattice defect formation mechanism and promote the stable expansion of the crystal surface. Specifically, the core role of borane-containing doping gas is to give diamond thin film specific semiconductor properties through controllable atomic replacement mechanism. Boron atoms produced by the decomposition of borane in a high-temperature environment preferentially occupy carbon atom sites in the diamond lattice with the help of the high-activity carbon-based atmosphere in the chemical vapor deposition process, forming an acceptor level and introducing hole carriers. This periodic doping strategy realizes the gradient distribution of boron atoms in the crystal growth direction through intermittent gas input, which not only avoids the excessive accumulation of lattice stress caused by continuous doping, but also ensures the controllable adjustment of carrier concentration in the depth direction of the film. During the doping process, the covalent bonding between boron atoms and carbon atoms is strengthened at high temperatures, effectively inhibiting the clustering of impurity atoms, and the active surface mobility in the pre-growth stage promotes the uniform embedding of boron atoms in the lattice, ultimately forming a diamond thin film with stable p-type semiconductor properties, laying the foundation for the electrical performance of subsequent device functionalization applications.
[0020] 2) The gradual decrease from the pre-growth temperature T0 to the end temperature T1 includes: gradually reducing the temperature at a rate of 3-8℃ / min; Using gradual cooling instead of constant temperature during deposition helps to form a dynamic thermodynamic deposition equilibrium environment, so that the surface diffusion behavior during growth is gradually controlled, and thermal stress concentration is reduced. At the same time, the cooling rate can regulate the adsorption and nucleation rate of carbon source on the crystal surface, promoting the expansion of single crystal region.
[0021] 3) During the cooling deposition stage, the growth rate of the diamond thin film is not less than 30μm / h.
[0022] Maintaining a growth rate of not less than 30μm / h during the cooling stage helps to maintain the stability of deposition kinetics and avoid the growth of amorphous regions or voids caused by low nucleation rate during the cooling process of the crystal surface.
[0023] The gradient cooling strategy of gradually reducing the pre-growth temperature to the end temperature is adopted in the present application, and the core function thereof is to balance the crystal growth quality and process efficiency by dynamically adjusting the thermodynamic environment. The high-temperature pre-growth stage forms a dense single crystal bottom layer by strengthening the carbon source cracking, and then the gradient cooling can effectively alleviate the lattice stress caused by sudden temperature change, and promote the orderly migration and arrangement of carbon atoms on the substrate surface. During the cooling process, the carbon atoms maintain a moderate migration ability under the controllable temperature field, which not only avoids the rapid proliferation of defects caused by high temperature, but also prevents the amorphous phase deposition caused by insufficient atomic kinetic energy at low temperature. The auxiliary gas applied synchronously continuously purifies the growth interface by selective etching, and cooperates with the gradient temperature control to inhibit the generation of impurity phase in a high-pressure environment, so as to realize the high-speed epitaxial growth of single crystal thin film, while ensuring the integrity of the crystal structure and the flatness of the surface.
[0024] After the above-mentioned optimized process, the infrared transmittance of the obtained diamond thin film material is not less than 80%, preferably not less than 82%, the crystal structure presents large-size single crystal quality, and the edge and center area have highly uniform lattice arrangement, which meets the application demand of area of 2.5 inches or more. The excellent performance is especially suitable for the substrate materials of infrared window, power device heat sink and high-frequency microwave device.
[0025] Preferably, the surface treatment in step S1 at least includes one of the following conditions: 1) pickling treatment: using an acid solution with a concentration of 55%-75% to perform pickling treatment on the surface of the substrate; 2) physical sputtering: using small molecule gas to perform physical sputtering on the surface of the substrate for 10-20s to form high-density uniform nucleation sites.
[0026] On the basis of selecting a suitable substrate material, surface treatment is also an important guarantee for high-quality and efficient generation of diamond thin film. The aforementioned pretreatment can form high-density and uniformly distributed nucleation sites as the position for the initial growth of diamond thin film atoms, and the small molecule gas treatment is used to ensure the number density of the nucleation sites. The small molecule gas is argon or nitrogen, and the physical sputtering power is 200-500W.
[0027] Preferably, in step S4, the annealing temperature T of the annealing treatment satisfies: T∈[max(0.9T 高 , 1.05T 低 ), min(1050℃, 1.1T 高 )]; Wherein, T 高 is the pre-growth temperature T0±50℃, and T 低The end temperature T1±25℃. The formula indicates that the lower limit of the temperature range of the annealing temperature T is the larger value between 0.9 times of T0±50℃ and 1.05 times of T1±25℃, and the upper limit of T is the smaller value between 1050℃ and 1.1 times of T0±50℃.
[0028] Preferably, the annealing process comprises at least one of condition (1) and condition (2): Condition (1), the ladder annealing process 2-5h, comprising: First-order annealing: annealing at (T 高 +T 低 ) / 2 to T 高 for 1-2h; Second-order annealing: annealing at T 低 to less than (T 高 +T 低 ) / 2 for 1-3h; Condition (2), alternatingly inputting hydrogen and argon, the flow ratio of hydrogen to argon being 1:(1-3), and each switching cycle being 10-30min.
[0029] In the chemical vapor deposition (CVD) process, temperature is an important factor affecting the reaction kinetics. Higher temperature usually increases the decomposition and diffusion rate of reactants, promoting crystal growth. But the rate of temperature change will affect the formation of crystal structure, rapid cooling may cause internal stress, while slow cooling helps the formation of ordered structure. In addition, maintaining a certain growth rate may require optimization of gas flow, pressure, temperature and other parameters to ensure sufficient carbon source supply and appropriate deposition conditions.
[0030] The conventional annealing process makes the atoms inside the diamond film obtain migration energy by heating, mainly used to eliminate the residual stress caused by temperature gradient or lattice mismatch during deposition, and repair point defects and line defects. At high temperature, the rearrangement of atoms can partially restore the integrity of the lattice, but the traditional method often uses fixed temperature annealing, which does not consider the matching of the thermal history of the deposition process, and is easy to lead to incomplete repair or local overburning.
[0031] The annealing process of the present application matches the temperature history of the deposition stage dynamically, which not only ensures that the annealing temperature is sufficient to activate the repair mechanism of bulk defects, but also avoids exceeding the diamond thermodynamic stability threshold to cause sp3 bond rupture. On this basis, the step annealing strategy is implemented in two stages: the first high-temperature annealing is aimed at the deep dislocation network formed in the pre-growth stage, and the dislocation climb and annihilation are realized through high-temperature atomic migration; the second low-temperature annealing focuses on the interface stress and surface micro-cracks accumulated in the cooling deposition stage, and the micro-defects are filled by vacancy diffusion and the residual stress is released. In addition, the introduction of hydrogen / argon alternating atmosphere forms a dynamic surface reconstruction mechanism: hydrogen passivates surface dangling bonds to inhibit amorphous carbon generation, argon inhibits hydrogen plasma over-etching, periodic switching promotes surface atom rearrangement to low-energy state, and finally realizes full-dimensional defect repair and interface optimization from bulk to surface, breaking through the repair limitations of traditional processes.
[0032] In a second aspect, the present application further provides a diamond thin film prepared by the above-mentioned method for preparing a diamond thin film.
[0033] Preferably, the infrared transmittance of the diamond thin film is not less than 80%, preferably not less than 82%.
[0034] Preferably, the crystal structure in the diamond thin film includes a large-size single crystal structure of not less than 2.5 inches.
[0035] Preferably, the large-size single crystal structure of not less than 2.5 inches accounts for at least 90% of the total volume of the crystal.
[0036] Preferably, the color of the diamond thin film material can reach gem grade.
[0037] In a third aspect, the present application further provides an application of the diamond thin film as a heat dissipation component.
[0038] Preferably, the diamond thin film is applied as a heat dissipation component in electronic components such as integrated circuits. The diamond thin film prepared by the present application has large-scale single crystal characteristics and high thermal conductivity, and can be used as a heat dissipation accessory for large-scale integrated circuits and other electronic components to improve the heat dissipation capacity of integrated circuits.
[0039] In addition, the diamond thin film of the present application can also be applied in high-frequency power devices, electrical sensing chips, and infrared optical window materials.
[0040] The technical solution of the present application at least includes the following beneficial effects: (1) The application synchronously completes the gas phase etching of amorphous carbon impurities and the single crystal preferential growth in the chemical vapor deposition process through the synergistic effect of the auxiliary gas with the preferred ratio. The Cl / F active components preferentially etch the grain boundary defects and non-diamond phases, the argon gas dilution controls the stability of the reaction atmosphere, the high pressure and high temperature environment enhances the carbon source cracking efficiency, and the high-speed epitaxial growth of the single crystal thin film is realized. Compared with the traditional impurity removal method which depends on multi-step acid etching, the application reduces the impurity generation from the source, avoids the lattice damage, and significantly improves the film transmittance and structural integrity through the in-situ auxiliary gas etching mechanism, thereby laying a structural foundation for subsequent functional application.
[0041] (2) The controlled chemical vapor deposition of the application includes high-temperature pre-growth and cooling deposition processes, and the temperature and pressure are controlled respectively, so that the balance between the crystal growth quality and the process efficiency is realized through dynamic adjustment of the thermodynamic environment. The high-temperature pre-growth process forms a dense single crystal bottom layer by strengthening the carbon source cracking, and then the gradient cooling can effectively relieve the lattice stress caused by sudden temperature change, and promote the ordered migration and arrangement of carbon atoms on the substrate surface. In the cooling deposition process, the carbon atoms maintain a moderate migration ability under the controllable temperature field, which not only avoids the rapid proliferation of defects caused by high temperature, but also prevents the deposition of amorphous phase caused by insufficient atomic kinetic energy at low temperature. The auxiliary gas applied synchronously continuously purifies the growth interface through selective etching, and in the high-pressure environment, the gradient temperature control cooperates to inhibit the generation of impurity phases, so as to realize the high-speed epitaxial growth of the single crystal thin film, and at the same time, guarantee the integrity of the crystal structure and the surface flatness.
[0042] (3) The annealing temperature range and the ladder / alternating atmosphere strategy are designed based on the thermal history of the deposition stage, so as to realize the full-dimensional defect repair from the bulk phase to the surface. The ladder annealing is processed by high temperature-low temperature in stages, respectively eliminating deep dislocation network and interface micro stress; the hydrogen / argon alternating atmosphere dynamically balances the surface reconstruction and etching loss, and an atomic level flat interface is obtained. This process forms a closed loop with the aforementioned auxiliary gas deposition system: the high-purity single crystal substrate in the deposition stage reduces the initial defect density, and the annealing stage repairs the residual micro defects, and the two cooperate to make the thin film have high crystalline quality and excellent electrical performance.
[0043] (4) The diamond thin film prepared by the method has the characteristics of high infrared transmittance, large-size single crystal structure and low defect density, and is particularly suitable for high-frequency power devices, electrical sensing chips and infrared optical windows and other multi-scene applications, and has good industrialization foundation. The film is measured, the large-size single crystal structure is more than 90vt%, the thermal conductivity is more than 1800 W / (m·K), the refractive index is more than 2.41, the infrared region (3-5 μm) transmittance is more than 80%, and it can be directly applied to power-intensive packaging, microwave windows and heat dissipation substrates and other fields with high requirements for material uniformity and structural integrity. BRIEF DESCRIPTION OF DRAWINGS
[0044] Figure 1 Flow chart of the method for preparing diamond thin film according to the present application; Figure 2 Figure for comparing the film color of the diamond thin film samples of Example 9 and Comparative Example 1, wherein a is the sample of Example 9 and b is the sample of Comparative Example 1; Figure 3 Figure for comparing the crystal structure of the diamond thin film samples of Example 9 and Comparative Example 2, wherein a is the sample of Example 9 and b is the sample of Comparative Example 2. DETAILED DESCRIPTION
[0045] In order to better understand the above technical solutions, the above technical solutions will be described in detail below in combination with the accompanying drawings and specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without making creative efforts fall within the scope of protection of the present application.
[0046] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise. "Plural" generally includes at least two.
[0047] It should also be noted that the terms "comprise", "contain" or any other variants thereof are intended to cover non-exclusive inclusion, so that the goods or devices comprising a series of elements not only include those elements, but also include other elements not explicitly listed, or include elements inherent to such goods or devices. Without more limitations, the element defined by the sentence "comprises a" does not exclude the presence of other identical elements in the goods or devices comprising the element.
[0048] The present application provides a method for preparing diamond thin film, which specifically comprises the following steps: S1, using a substrate material matching the lattice constant of diamond thin film material as a substrate, and performing surface treatment on the substrate: 1.1) Substrate preparation: selecting a substrate material matching the lattice constant of diamond thin film as a substrate, the substrate is preferably natural diamond single crystal, diamond single crystal prepared by HPHT method or CVD diamond single crystal. The crystal face direction of the substrate is preferably (100) or (111), and a high orientation surface structure is obtained by crystal face orientation cutting.
[0049] 1.2) Surface treatment: including acid pickling treatment and / or physical sputtering treatment, preferably acid pickling treatment and physical sputtering treatment are carried out in sequence: 1.2.1) Acid pickling treatment, mixed acid solution with a concentration of 55%-75% is used to remove surface impurities, the mixed acid can be selected from a combination of concentrated hydrochloric acid and hydrofluoric acid with a volume ratio of (5-10):1, a combination of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of (3-5):1, or a three-acid combination of concentrated hydrochloric acid, hydrofluoric acid and concentrated nitric acid; 1.2.2) Physical sputtering, small molecule gases such as argon and hydrogen are introduced and a low-pressure plasma excitation with a power of 200-500W is applied for 10-20s to generate a large number of high-density nucleation sites. These nucleation sites serve as preferential growth sites for subsequent deposition of carbon sources, which helps to improve the uniformity of nucleation and the consistency of orientation of single crystal structure.
[0050] S2, by introducing a specific ratio of mixed reaction gas into the deposition chamber, an appropriate gas phase reaction atmosphere is established. The composition of the mixed gas includes 80%-95% hydrogen, 3%-8% methane and 2%-12% auxiliary gas by volume percentage, preferably the mixed reaction gas is composed of 85%-91% hydrogen, 3%-5% methane and 6%-10% auxiliary gas; The auxiliary gas at least includes one of argon, chlorine, hydrogen fluoride and hydrogen chloride, preferably combined as argon:chlorine:hydrogen fluoride=1:(0.5-1.5):(0.3-1).
[0051] Wherein hydrogen and methane provide carbon source and reducing atmosphere, and Cl· and F· free radicals released by chlorine and hydrogen fluoride at high temperature can preferentially react with amorphous carbon or impurities to generate volatile byproducts (such as CCl4, CF4) to remove from the gas phase, thereby achieving in-situ etching and purification at the growth interface, and argon as an inert diluent component helps to control the plasma density and atmosphere stability, and overall improves the interface quality and crystal selectivity of epitaxial growth.
[0052] S3, controlled chemical vapor deposition for growing diamond thin film, including being carried out at 850℃-1000℃, chamber pressure not less than 21 kPa, preferably 24-30 kPa, and adopting a two-stage temperature control strategy to optimize deposition kinetics: 3.1) High-temperature pre-growth: maintain chamber pressure P0≥25kPa, preferably P0 not less than 27kPa, pre-growth temperature T0 controlled at 950℃-1000℃, this stage time accounts for 25%-55% of the total controlled chemical vapor deposition time, mainly for forming a dense, highly directional single crystal initial layer; optionally, introducing boron-containing doping gas for boron doping control. Preferably, periodically introduce boron-containing gas, doping concentration controlled at 1×10 18 to 5×10 20 cm-3 The doping period is 5-15 min. 3.2) Deposition with temperature decreasing: the chamber pressure P1 is kept at P0-3 kPa, preferably P1 is not less than 24 kPa, and the temperature is gradually decreased from the pre-growth temperature T0 to the end temperature T1, which is about 50-100℃ lower than the pre-growth temperature T0. The temperature decreasing rate is controlled at 3-8℃ / min, which helps to stabilize the carbon atom diffusion path on the surface, improve the lattice integrity and reduce stress concentration. During the whole deposition process with temperature decreasing, the thin film growth rate is preferably not less than 30 μm / h to ensure the process efficiency and flexibility of thickness control.
[0053] S4, annealing treatment: after deposition, the obtained diamond thin film needs to be subjected to heat annealing treatment to release internal stress, repair defects and improve crystalline quality.
[0054] The annealing temperature T is in the range of [max(0.9T 高 , 1.05T 低 ), min(1050℃, 1.1T 高 )]. Wherein, T 高 is the pre-growth temperature T0±50℃, and T 低 is the end temperature T1±25℃. The lower limit of the temperature range of the annealing temperature T is the larger value between 0.9 times of T0±50℃ and 1.05 times of T1±25℃, and the upper limit of T is the smaller value between 1050℃ and 1.1 times of T0±50℃. Preferably, the annealing treatment specifically includes the following process conditions: Condition (1), step annealing treatment for 2-5h, including: First-order annealing: annealing at (T 高 +T 低 ) / 2 to T 高 for 1-2h; Second-order annealing: annealing at T 低 to less than (T 高 +T 低 ) / 2 for 1-3h; Condition (2), periodically alternating the input of hydrogen and argon during the annealing process, the hydrogen / argon volume flow ratio is 1:(1-3), and the switching period is 10-30 min.
[0055] The diamond thin film material obtained by the above preparation method has multiple characteristics such as high infrared transmittance, large-size single crystal structure and low defect density. The infrared transmittance is not less than 80%, preferably not less than 82%. The crystal structure presents large-size single crystal quality, and the edge and center area have highly uniform lattice arrangement, meeting the application demand of an area of 2.5 inches or more. Moreover, the thickness of the diamond thin film can be controlled according to the demand by controlling the process parameters. The above excellent performance enables the diamond thin film to be used as a heat dissipation component in multiple fields such as electronic components, for example, as an integrated circuit heat sink, a power device heat sink, and also as an infrared window material, a high-frequency microwave device, etc.
[0056] Example 1 Example 1 prepares a diamond thin film sample by the following steps, specifically including: S1, using a natural diamond single crystal as a substrate, and performing surface treatment on the substrate: 1) acid washing treatment, using a mixed acid solution with a concentration of 65wt% to remove surface impurities, the mixed acid being concentrated hydrochloric acid and hydrofluoric acid in a volume ratio of 8:1; 2) physical sputtering, introducing argon and hydrogen in a volume ratio of 4:1, and applying a power of 350W low-pressure plasma excitation for 15s to generate a large number of high-density nucleation sites.
[0057] S2, introducing mixed reaction gas into the deposition chamber to establish a suitable gas phase reaction atmosphere: containing 80% hydrogen, 8% methane and 12% auxiliary gas by volume percentage, wherein the auxiliary gas is argon, chlorine, hydrogen fluoride and hydrogen chloride premixed in a volume ratio of 1:1:1:1.
[0058] S3, controlled chemical vapor deposition to grow diamond thin film, using a two-stage temperature and pressure control deposition strategy: 1) high-temperature pre-growth: maintaining the chamber pressure P0 at 25kPa, and controlling the pre-growth temperature T0 at 975±5℃, the stage time accounting for 40% of the total controlled chemical vapor deposition time; 2) temperature reduction deposition: maintaining the chamber pressure P1 at 22kPa, gradually reducing the temperature from the pre-growth temperature T0 to the end temperature T1, the end temperature T1 being 900±5℃, and the temperature reduction rate being controlled at about 5℃ / min, and the thin film growth rate being preferably not less than 30μm / h during the whole temperature reduction deposition process.
[0059] S4, annealing treatment: after deposition, the obtained diamond thin film needs to be subjected to heat annealing treatment, during which hydrogen and argon are periodically alternately introduced, the hydrogen / argon volume flow ratio being 1:2, the switching period being 30min, and a step annealing method is adopted, including: First annealing: annealing at 945±5℃ for 1.5h; Second annealing: annealing at 925±℃ for 1.5h.
[0060] Examples 2-18 The process conditions of Examples 2-18 are the same as Example 1, except that the mixed reaction gas composition is different, as shown in Table 1.
[0061] Table 1 List of mixed reaction gas compositions of Examples 1-18
[0062] Examples 19-25 Examples 19-25 are based on the mixed reaction gas composition of Example 9, and differ from Example 9 in that the process parameters in the preparation method are adjusted, as shown in Table 2.
[0063] Table 2 List of partial process parameters of Example 9 and Examples 19-25
[0064]
[0065] Comparative Example 1 Comparative Example 1 differs from Example 9 in that no auxiliary gas is used, and the mixed reaction gas only contains 90% hydrogen and 10% methane by volume percentage.
[0066] Comparative Example 2 Comparative Example 2 differs from Example 9 in that an auxiliary gas is used, but the amount is relatively low, and the mixed reaction gas is: 90.5% hydrogen, 8% methane, and 1.5% auxiliary gas, wherein the auxiliary gas is argon (0.6%), chlorine (0.6%), and hydrogen fluoride (0.3%) premixed at a volume ratio of 1:1:0.5.
[0067] Comparative Example 3 Comparative Example 3 differs from Example 9 in that the controlled chemical vapor deposition conditions are different. Comparative Example 3 uses a single deposition condition: deposition at 900±5℃ and a pressure of 23kPa for 25min.
[0068] Comparative Example 4 Comparative Example 4 differs from Example 9 in that only argon is passed during the annealing stage of Comparative Example 4, and a single annealing method is used, i.e. annealing at 925±5℃ for 3h.
[0069] Testing and Results The samples of Examples 1-25 and Comparative Examples 1-4 were tested as follows, with 3 samples prepared for each group for parallel testing and the average value taken, and the test results are shown in Table 3.
[0070] 1. Test the color, refractive index and infrared transmittance of the thin film Each sample is irradiated by cathode rays, and the different colors of fluorescence emitted by each sample are observed: (1) The diamond thin film sample of Example 1-25 is white and transparent and has no fluorescence; (2) The sample of Comparative Example 1 does not use auxiliary gas and exhibits obvious yellow-green fluorescence, and the sample of Comparative Example 2 also exhibits lighter yellow-green fluorescence due to the small amount of auxiliary gas used; (3) The samples of Comparative Examples 3 and 4 have no fluorescence, but the chroma and transparency are obviously lower than those of each example.
[0071] 2. Crystal structure test, using Raman spectroscopy (XRD can also be used).
[0072] 3. Thermal conductivity test, using laser flash method.
[0073] Table 3 Test results of Examples 1-25 and Comparative Examples 1-4
[0074] By comparing the test results and referring to Figures 2-3 It can be seen that the sample of the example of the present application is white and has no fluorescence, the refractive index is above 2.41, preferably above 2.42, the infrared transmittance is above 80%, preferably above 82%, the proportion of large-size single crystal structure is above 90%, preferably above 91%, the thermal conductivity is above 1800 W / (m·K), preferably above 2000 W / (m·K), more preferably above 2010 W / (m·K).
[0075] Although the preferred embodiments of the present application have been described, those skilled in the art can make further changes and modifications to these embodiments once they know the basic inventive concept. Therefore, the appended claims are intended to be interpreted as including all changes and modifications falling within the scope of the present application. Obviously, those skilled in the art can make various modifications and changes to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and changes of the present application fall within the scope of the claims of the present application and their equivalents, the present application also intends to include these modifications and changes.
Claims
1. A method for preparing a diamond film, characterized in that: The following steps are involved: S1. Using a substrate material having a lattice constant matching that of the diamond film material as a substrate and performing surface treatment on the substrate; S2. introducing a mixed reaction gas comprising, by volume percentage, 80%-95% hydrogen, 3%-8% methane, and 2%-12% auxiliary gas; the auxiliary gas comprising at least one of argon, chlorine, hydrogen fluoride, and hydrogen chloride; S3, performing controlled chemical vapor deposition at 850° C.-1000° C. and a pressure of not less than 21 kPa to grow a diamond film on the substrate surface; S4. Annealing the diamond film.
2. The preparation method according to claim 1, wherein The substrate material is selected from natural diamond single crystal, HPHT diamond single crystal or CVD diamond single crystal, and the surface of the seed crystal is subjected to (100) or (111) crystal plane orientation cutting treatment.
3. The preparation method according to claim 1 or 2, wherein In step S2, the auxiliary gas is composed of argon, chlorine, and hydrogen fluoride in a volume ratio of 1:(0.5-1.5):(0.3-1).
4. The preparation method according to claim 3, wherein The controlled chemical vapor deposition in step S3 includes: 1) High-temperature pre-growth: The high-temperature pre-growth is carried out at a pre-growth temperature T0 of 950°C-1000°C, and the chamber pressure P0 is maintained at ≥25kPa. The duration of the high-temperature pre-growth is 25%-55% of the total controlled chemical vapor deposition time; 2) Cooling deposition: The temperature is gradually reduced from the pre-growth temperature T0 to the end temperature T1 for deposition. The end temperature T1 is T0-100℃ to T0-50℃, and the chamber pressure P1 is maintained at P0-3kPa.
5. The preparation method according to claim 4, wherein Controlled chemical vapor deposition includes at least one of the following conditions: 1) During the high-temperature pre-growth process, borane-containing doping gas is periodically introduced, and the boron doping concentration is 1×10 18 to 5×10 20 cm -3 ; 2) gradually lowering the temperature from the pre-growth temperature T0 to the final temperature T1, including: gradually lowering the temperature at a rate of 3-8°C / min; 3) During the cooling deposition process, the growth rate of the diamond film is not less than 30μm / h.
6. The preparation method according to claim 4 or 5, characterized in that The surface treatment in step S1 includes at least one of the following conditions: 1) Pickling treatment: Use an acid solution with a concentration of 55%-75% to pickle the substrate surface; 2) Physical sputtering: Use small molecule gas to perform physical sputtering on the substrate surface for 10-20s to form high-density uniform nucleation sites.
7. The preparation method according to claim 4 or 5, characterized in that In step S4, the annealing temperature T of the annealing treatment satisfies: T∈[max(0.9T 高 , 1.05T 低 ),min(1050℃ , 1.1T 高 )]; Among them, T 高 is the pre-growth temperature T0±50℃, T 低 The ending temperature is T1±25℃.
8. The preparation method according to claim 7, wherein The annealing treatment includes at least one of conditions (1) and (2): Condition (1) Step annealing for 2-5 hours, including: First-order annealing: at (T 高 +T 低 ) / 2 to T 高 Annealing temperature range 1-2h; Second-stage annealing: at T 低 to less than (T 高 +T 低 ) / 2 temperature range annealing 1-3h; Condition (2) Hydrogen and argon were introduced alternately, with the hydrogen flow rate to argon flow rate ratio being 1:(1-3), and each switching cycle being 10-30 minutes.
9. A diamond film, characterized in that: The diamond film is prepared by the method for preparing the diamond film according to any one of claims 1 to 8.
10. Use of the diamond film according to claim 9 as a heat dissipation component.
Citation Information
Patent Citations
Method for improving splicing growth quality of large-area monocrystal diamond
CN115874282A
Single crystal diamond and preparation method and application thereof
CN119800501A
Preparation method of polycrystalline diamond sheet and polycrystalline diamond sheet
CN120400996A
Electronic device grade single crystal diamonds and method of producing the same
US20160201221A1
Cited By
Temperature control method and system for CVD (Chemical Vapor Deposition) equipment
CN121087466A
High-strength and high-toughness polycrystalline diamond compact rich in FCC phase high-entropy alloy
CN121870090A
A high-strength and high-toughness polycrystalline diamond compact rich in fcc phase high-entropy alloy
CN121870090B